Negosiasi Identitas Budaya Mahasiswa Papua dalam Komunitas Mahasiswa Rantau di Yogyakarta: Kajian Model Identity Negotiation Theory Ting-Toomey - fauzi, akmal ahmad; Kartinawati, Erwin (Samsara Institute Publisher, 2025)
This study explores the dynamics of intercultural communication among Papuan students living within diverse student communities in Yogyakarta. Employing a qualitative approach and case study method, the research aims to understand how Papuan students negotiate their cultural identities in a majority non-Papuan cultural environment. Stella Ting-Toomey’s Identity Negotiation Theory serves as the main analytical framework. The findings reveal that cultural identity is negotiated through symbolism, adaptive communication strategies, and the formation of safe community spaces. This research contributes to the underexplored discourse of intra-national intercultural communication studies in Indonesia.